2023
DOI: 10.1097/bpo.0000000000002383
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multicenter Study of Developmental Dysplasia of the Hip: What Can Patients Expect After Open Reduction?

Abstract: Background: Although there are several predominantly single-center case series in the literature, relatively little prospectively collected data exist regarding the outcomes of open hip reduction (OR) for infantile developmental dysplasia of the hip (DDH). The purpose of this prospective, multi-center study was to determine the outcomes after OR in a diverse patient population. Methods: The prospectively collected database of an international multicenter study group was queried for all patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, this prospective, multicentre study from a clinical outcomes team in Philadelphia (Pennsylvania, USA) aimed to investigate the outcomes of open reduction (OR) for infantile developmental dysplasia of the hip (DDH). 1 This is an interesting study that provides insights into expectations based on current evidence. The paper is the largest multicentre study to date, with a minimum follow-up of one year.…”
Section: Developmental Dysplasia Of the Hip: What Can Patients Expect...mentioning
confidence: 99%
“…However, this prospective, multicentre study from a clinical outcomes team in Philadelphia (Pennsylvania, USA) aimed to investigate the outcomes of open reduction (OR) for infantile developmental dysplasia of the hip (DDH). 1 This is an interesting study that provides insights into expectations based on current evidence. The paper is the largest multicentre study to date, with a minimum follow-up of one year.…”
Section: Developmental Dysplasia Of the Hip: What Can Patients Expect...mentioning
confidence: 99%
“…Patients with developmental hip dislocations that fail conservative management or present late often require surgical intervention in the form of closed or open reduction and hip spica casting. 3,4 Magnetic resonance imaging (MRI) is often used postoperatively to confirm the reduction in the spica cast without exposure to ionizing radiation and allows for excellent visualization of the cartilaginous femoral head in patients that have not yet formed an ossific nucleus. 5 In addition to images obtained immediately postoperatively, MRI at subsequent time intervals may be used to confirm maintenance of hip reduction and can also show improvement of the femoral head position within the acetabulum.…”
mentioning
confidence: 99%
“…6 Current existing literature describes changes in acetabular morphology in patients with DDH after reduction, but there is a paucity of research on femoral head changes. 4,7,8 This may be due to difficulties in quantitatively measuring femoral head shape in addition to lack of multiplanar imaging at regular time points after reduction. Using hip arthrograms and MRIs, previous studies have demonstrated dysplasia and lack of sphericity of the femoral head in patients with DDH at the time of reduction.…”
mentioning
confidence: 99%
See 2 more Smart Citations